Evaluasi Numerik Kekuatan Struktur Baja Gable Frame Dengan Rafter WF Lurus Terhadap Beban Seismik - Chandara, Kumala; Ramlan Wijaya, Taufik (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2025)
The structural performance of straight WF rafter gable frames with spans of 16 m and 24 m under static and seismic loadings according to SNI 1726:2019 was conducted in this study. The numerical analysis used solid finite elements provided in ANSYS by focusing on deformation, drift ratio, maximum stress, and stress ratio (SR). The results indicate that for the 16 m span, the straight WF rafters remain within strength and serviceability limits with drift ratios of 0.237–0.285% and maximum stresses of 244.64–279.77 MPa. However, for the 24 m span, deformation increases to drift ratios of 0.421–0.442% and stresses of 232.95–259.95 MPa, causing some models to exceed the SNI limit and the yield strength limitation (SR > 1). Therefore, in earthquake-sensitive areas, straight WF rafters are recommended only for gable frames with short to medium spans. Meanwhile longer spans require modified profiles or alternative structural systems to satisfy strength and serviceability criteria.